A low-frequency hybrid energy harvester with high output performance. (November 2015) - Xia, Y; Liu, W; Chen, T; Yang, Z; Wang, P; Liu, H; Sun, L
Abstract: Harvesting energy from ambient environment as a power source has attracted a wide attention now. However, it meets with difficulties of achieving high output performance under low excitation frequency. This paper presents a low-frequency hybrid energy harvester with high output performance based on frequency-up-conversion (FUC) approach. Under the strike of electromagnetic harvesting suspension structure, the PVDF cantilevers can operate at their resonant frequency with larger amplitude. The power output and energy conversion efficiency can be improved significantly at low frequency excitation. For an excitation acceleration of 0.5g, the peak voltage output of electromagnetic part can reach to 1.9 V at driving frequency of 23.6 Hz. In addition, the peak voltage of PVDF cantilever increases from 30 mV to 3 V and the working frequency increase from 23.6 Hz to 60.6 Hz by using FUC approach.